RehabNet: a social network for the deployment of online rehabilitation content - Vieira, Artur César Nunes (2017)
Social network sites (SNSs) have gained much popularity and attention of academic and industry researchers intrigued by the opportunities they give people to reach others in an easy and timely manner, to exchange and share various kinds of information. As recognition of this fact, there has been a growing attention over the last years in the development of health social networks and their impact on the people. However current health social networks suffer different limitations related with their functionality and usability. Furthermore, the majority of these health social networks only meet present information about treatments and symptoms, and do not are designed for health professionals and researchers. This work presents the implementation of a health social network which aims at filling existing gaps, allowing people to have a direct interaction with the health professionals and the possibility to participate from home in training activities and research studies to improve their recovery. Additionally, offers health professionals and researchers the possibility to create and deploy new types of trainings and assess the impact in the recovery of people. Surveys and usability tests were performed to validate the conceptual and design ideas.